[Kennedy, Nigel (violinist) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Nigel Kennedy (born 28 December 1956) is an English violinist and violist. He made his early career in the classical field, and has more recently performed in jazz, klezmer and other music genres. He has toured to Australia on many occasions, and performed with the Sydney Symphony Orchestra - further material featuring Kennedy is located in the separate PROMPT collection under the Sydney Symphony Orchestra.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Kennedy, Nigel -- Miscellanea; Violin -- Performance -- Miscellanea; Violinists -- Miscellanea; Violists -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian